2018
DOI: 10.1016/j.neuron.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory Enhances Cortical Representations via Spatially Specific Coordination of Spike Times

Abstract: The online maintenance and manipulation of information in working memory (WM) is essential for guiding behavior based on our goals. Understanding how WM alters sensory processing in pursuit of different behavioral objectives is therefore crucial to establish the neural basis of our goal-directed behavior. Here we show that, in the middle temporal (MT) area of rhesus monkeys, the power of the local field potentials in the αβ band (8-25 Hz) increases, reflecting the remembered location and the animal's performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 54 publications
7
45
0
Order By: Relevance
“…Our data do not directly address this point, but the entrainment changes reported here, particularly during 20-Hz stimulation, are comparable to those linked with behavioral changes. Specifically, increases of ∼0.1 PLV have been associated with changes in sensory representations and working memory (64,65), perceptual organization (2), behavioral state (66), learning and reward expectancy (67), and the retrieval of memories (68). Changes in synchronous activity appear to underlie momentary lapses in performance (4) and serious pathological conditions (5), so even small changes in spike timing, when distributed across a network of neurons, may exert a powerful influence on behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Our data do not directly address this point, but the entrainment changes reported here, particularly during 20-Hz stimulation, are comparable to those linked with behavioral changes. Specifically, increases of ∼0.1 PLV have been associated with changes in sensory representations and working memory (64,65), perceptual organization (2), behavioral state (66), learning and reward expectancy (67), and the retrieval of memories (68). Changes in synchronous activity appear to underlie momentary lapses in performance (4) and serious pathological conditions (5), so even small changes in spike timing, when distributed across a network of neurons, may exert a powerful influence on behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Attention studies have looked at neurons receiving diverse top–down signals, and reported both correlation and decorrelation effects 11 ; indeed, fluctuations in the attentional state have also been shown to contribute to cross-trial variability 12, 13 . Our recent work 14, 15 has shown that during spatial working memory (WM), extrastriate visual areas receive a top–down WM signal from the prefrontal cortex (PFC) and undergo subthreshold modulations based on the content of WM (see Supplementary Note 1 for more details).…”
Section: Introductionmentioning
confidence: 99%
“…We calculated PPL for each time and frequency according to equation 2 were pooled together, and then we used the vector averaging method to calculate the SPL magnitude. In order to control for any effects of different numbers of spikes and trials between the two conditions, we considered a fixed window of 15 spikes and measured the SPL magnitude for the spikes of each window, and then took the mean across these windows 46 .…”
Section: Discussionmentioning
confidence: 99%